Assessment of foetal cardiac function by myocardial tissue doppler in foetal growth restriction - Basu, Barnali; Shetty, Ranjan; Gupta, Krishnendu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: One of the consequences of IUGR is the development of cardiac diastolic dysfunction in fetuses. Tissue doppler in echocardiography is a new technique to detect myocardial tissue function and can act as a useful tool in the identification of this complication. Hence we decided to undertake this study to assess the utility of myocardial tissue doppler in detecting foetal cardiac dysfunction in IUGR. It was a prospective case control study in a tertiary care teaching hospital. Methods: Foetal cardiac function in the third trimester of pregnancy was evaluated with the help of myocardial tissue doppler and compared between IUGR and normal growth babies and correlated with vessel doppler findings and neonatal outcomes. Results: There were sixty two IUGR and fifty eight normal growth babies in the study. In babies with IUGR, particularly the ones with severe IUGR, abnormal vessel doppler and adverse neonatal outcomes, right ventricular MPI was found to be significantly lower. However, the variable had a poor sensitivity (40%) in detecting fetuses at risk for poor neonatal outcomes. Conclusions: Myocardial tissue doppler shows right sided cardiac dysfunction in IUGR babies in comparison to normal growth babies It is however not a sensitive indicator of adverse perinatal outcome in IUGR babies.